Evaluation of Peripartum Hysterectomy in a Tertiary Care Unit and Its Effect on Patients’ Long-Term Physical and Mental Wellbeing: Quest Is Not Over When You Save the Life - P. D. M. Pathiraja; Asanka Jayawardane (Obstetrics and Gynecology International)
Objectives. Peripartum hysterectomy can be performed as an elective procedure or as a life-saving emergency procedure in obstetrics. It is associated with significant maternal morbidity and mortality. We report peripartum hysterectomies done during the study period in a tertiary referral centre, Colombo, Sri Lanka. Methodology. We collected data on all severe acute maternal morbidity and mortality events (SAMM) from June 01, 2014, to June 01, 2015, at De Soysa Hospital for Women (DSHW). We invited all women who underwent PPH to complete the 36-Item Short Form Health Survey questionnaire (SF-36) before hospital discharge and at six months after the hysterectomy date to assess their general and mental health before and after surgery. Focus group discussions (FGD) were used to further evaluate the patient experience and to identify service delivery improvements. Results. There were eleven peripartum hysterectomies done during the study period for 7160 deliveries. None were primigravida. Median age and gestation were 36 years and 37 weeks, respectively. The commonest indication for peripartum hysterectomy was a morbidly adherent placenta (seven). Nine of the deliveries were elective lower-segment caesarean section and two were vaginal deliveries. Four emergency peripartum hysterectomies were done for primary postpartum haemorrhage (PPH) and two for secondary PPH. All patients required intensive care and there were no maternal deaths. The analysis of SF-36 data revealed that all patients suffered a significant reduction in the quality of life at six months after the surgery. FGD highlighted that most patients needed further counselling and support to improve their physical, psychological, and social wellbeing. Some of the patients were willing to share their experience on voluntary basis to help those undergoing peripartum hysterectomies in the future. Conclusion. Peripartum hysterectomy is an important life-saving procedure associated with severe maternal morbidity and mortality. This study reveals that the physical, psychological, and social adverse effects would remain in the long term.